2013
DOI: 10.1186/1471-2458-13-46
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and acceptability of cervical cancer screening among HIV positive Nigerian women

Abstract: BackgroundThe proven benefit of integrating cervical cancer screening programme into HIV care has led to its adoption as a standard of care. However this is not operational in most HIV clinics in Nigeria. Of the various reasons given for non-implementation, none is backed by scientific evidence. This study was conducted to assess the willingness and acceptability of cervical cancer screening among HIV positive Nigerian women.MethodsA cross sectional study of HIV positive women attending a large HIV treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
83
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 16 publications
25
83
9
Order By: Relevance
“…16 That study found previous cervical cancer screening very low at 9.7% but a significant increase to 79.8% after joining the clinic.…”
Section: Discussionmentioning
confidence: 84%
“…16 That study found previous cervical cancer screening very low at 9.7% but a significant increase to 79.8% after joining the clinic.…”
Section: Discussionmentioning
confidence: 84%
“…91,102,112,113 Loss to follow-up after initial diagnosis is high, and treatment opportunities are missed. 96,114 Integrating ICC screening and treatment with HIV services could offer improved uptake of screening and treatment outcomes.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…The Advances in Screening and Prevention in Reproductive Cancers (ASPIRE) project, based in Uganda, was developed to examine innovations in cancer prevention for women in LMIC [14–17]. Although other studies in sub-Saharan Africa have examined attitudes of WHIV to cervical cancer screening, none have specifically addressed self-collection of HPV as a screening modality in this population [18]. To further understand the attitudes of WHIV towards self-collected specimens for cervical cancer screening, we surveyed WHIV in Kisenyi, Uganda, to explore their intention to participate in self-collection based cervical cancer screening, and offered women self-collection based testing at the local HIV clinic.…”
Section: Introductionmentioning
confidence: 99%